Correlation between Central Vena Pressure Measurement with Collapsibility Index of Internal Jugular Veins in Critically ill Patients - Tjokorda Gde Agung Senapathi (Journal of Global Pharma Technology, 2019)
Background: Central venous pressure (CVP) is popular for assessing fluid estimation, especially critically ill patients. Another method in assessing the CVP today is by using ultrasonic cardiac output monitors (USCOM) using transaortic or transpulmonary Doppler’s ultrasound. The objective of this study was to determine the correlation between CVP and IJV collapsibility index to monitor the adequacy of the intravascular volume status in critically ill patients in ICU. Patients and Method: This analytic, cross-sectional study involved 70 patients of 19 to 64 years. The internal jugular vein (IJV) collapsibility index was examined with ultrasound cardiac output monitoring (USCOM) to assess the patient's intravascular volume status, then the data was compared to CVP. The Spearman rank correlation was used to test the hypothesis. Results: The subjects consisted of 38 males and 32 females, with an age range of 19-64 years. The Spearman’s rank correlation test showed a statistically negative correlation between the CVP value and the internal jugular venous pressure index collapsibility value (R=-0.844, p <0.001). Conclusion: There is a strong negative correlation between IJV collapsibility index and CVP in patients treated in the ICU.Keywords: Hemodynamics, Volume status, CVP, USCOM, Collapsibility index.